Whose Voice is That?: Issues of Identity, Voice and Representation Arising in an Ethnographic Study of the Lives of Disabled Teenagers who use Augmentative and Alternative Communication (AAC) - Wickenden, Mary (Disability Studies Quarterly, 2011)
Keywords Alternative and augmentative communication (AAC), authorship, ethnography, co-constructed conversations, identity, representation, teenagers, voice Abstract This paper presents findings about identity, voice and representation arising from a broader ethnographic study with disabled teenagers who use AAC. This was informed by theory from childhood studies, disability studies and anthropology. The author spent 18 months carrying out qualitative, predominantly ethnographic, research with teenagers aged 10-19 years who use AAC. Participant observation and extended narrative conversations with 9 key young people, in a variety of contexts yielded rich data about how they see themselves and how they are seen by others. Additional input from other teenage AAC users, parents and school staff contextualize this. Three adult AAC users were research advisors, and their commentary at many stages of the study was helpful. This paper focuses more narrowly on specific aspects of aided communication, how the teenagers perceive that their use of AAC impacts on their identities, how individuals' voices emerge in co-constructed conversations and issues around representation.